1964
DOI: 10.1180/minmag.1964.033.265.09
|View full text |Cite
|
Sign up to set email alerts
|

The oriented transformation of aragonite into calcite

Abstract: T HE anhydrous carbonates of metals may be divided into two groups: CaCO 8 exists in both groups as calcite and aragonite. Divalent metals having smaller ionic radii than that of calcium belong to the calcite series. The others, with greater ionic radii, are members of the aragonite series. The structures of calcite and aragonite were analysed by Bragg (1914Bragg ( , 1924. In calcite, the Ca ions are arranged in a cubic close-packed (ABCABCA...) way in layers perpendicular to the threefold axis of the rhombohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The presence of well‐preserved aragonite material gives an indirect hint of the state of preservation of the biogenic calcite. In fact, aragonite is a metastable carbonate polymorph and tends to turn quickly into the more stable calcite in the presence of fluids and increasing temperature, for example during advanced diagenesis (Dasgupta ; Boettcher & Wyllie ; Putnis & Putnis ). According to the results, the OSL of the studied Sphenoceramus specimens mostly emitted very dull CL and retained faint growth patterns and original shell microstructures (prisms).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of well‐preserved aragonite material gives an indirect hint of the state of preservation of the biogenic calcite. In fact, aragonite is a metastable carbonate polymorph and tends to turn quickly into the more stable calcite in the presence of fluids and increasing temperature, for example during advanced diagenesis (Dasgupta ; Boettcher & Wyllie ; Putnis & Putnis ). According to the results, the OSL of the studied Sphenoceramus specimens mostly emitted very dull CL and retained faint growth patterns and original shell microstructures (prisms).…”
Section: Discussionmentioning
confidence: 99%
“…This ' 'calcining" usually spreads from random nucleation points but may spread from a split in the carbonate, from a sub-grain boundary or from Big. 5 There is a strongly preferred orientation of the oxide with respect to the carbonate if the calcining occurs gradually (<lo00 A per second advance of the carbonate-oxide boundary). The close-packed calcium layers of the carbonates remain in the same orientation in the oxide, the carbon dioxide being expelled between them as in Fig.…”
Section: Decomposition Of the Earbonatementioning
confidence: 99%
“…Dasgupta [ 5 ] using X-ray diffraction observed that the orientation of the calcium layers remains fixed during the transformation with displacement of the close-packed calcium planes and rotation of the CO, groups.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, absence of any other major peaks indicated that incinerated conch was in pure calcite form. Previous X ray diffraction studies of aragonite crystal showed that aragonite was successfully transformed to calcite by heating above 488 °C [34]. It has been reported that calcium in calcium carbonate calcite form is better absorbed as compared to its aragonite form [35].…”
Section: Discussionmentioning
confidence: 99%